CONSTANT CAPACITANCE TECHNIQUE TO STUDY ELECTRICAL INSTABILITIES IN INP MIS PROVIDED BY PECVD SILICON-NITRIDE - KIM, CH; KWON, SD; CHOE, BD; HAN, IK; LEE, JI; KANG, KN; PARK, HL; LIM, H (ELSEVIER SCIENCE BV, 1993)
The charge trapping behaviour in silicon nitride/InP metal insulator semiconductor (MIS) capacitors is investigated by a constant capacitance technique at room temperature. Silicon nitride films were formed by a conventional plasma enhanced chemical vapor deposition (PECVD) technique where MIS structures were grown simultaneously on n- and p-type InP to observe the effect of electron and hole trapping, respectively. We have found that the carrier trapping by direct tunneling near the silicon nitride/InP interface is dominant under low insulator fields for both n- and p-type samples. The amount of injected charges was similar for both types of MIS prepared under same condition. This behaviour is attributed to the amphoteric nature of silicon dangling bonds. The injection of carriers to the bulk of the silicon nitride assisted by the electric field occurs at high insulator fields. This phenomena is apparent particularly for MIS diodes prepared with a smaller ammonia to silane partial pressure ratio in deposition. It is also confirmed that the trap density near the silicon nitride/InP interface is about one order of magnitude higher than that of the silicon nitride bulk due to the initial transient phenomena of the PECVD process.
Keywords: CHEMICAL VAPOR-DEPOSITION; DEEP TRAP; DEFECTS; SI3N4; FILMS